Preparation process of amine liquid purification resin for carbon capture system
By using the amine liquid purification resin optimized by the preparation process in the carbon capture system, the carbon capture efficiency reduction and equipment corrosion problems caused by the accumulation of thermally stable salt in the amine liquid are solved, and more efficient thermally stable salt removal and equipment protection effects are achieved.
Patent Information
- Application Number
- CN202510318258.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
In the existing carbon capture system, after amine liquid comes into contact with complex flue gas components for a long time, it will generate thermally stable salts, resulting in reduced carbon capture efficiency and equipment corrosion, and increase maintenance costs.
A preparation process for purifying resin with an amine liquid with a carbon capture system is adopted. By combining monomers such as styrene, divinylbenzene, acrylate, etc. with pore-generating agents, initiators, etc., polystyrene microspheres with optimized pore structure are formed, and the adsorption efficiency of the resin is improved through chloromethylation and aminoation treatment.
It significantly improves the removal rate of thermally stable salts in amine liquid, extends the service life of the equipment, reduces maintenance costs, and improves the overall performance of the carbon capture system.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of carbon capture, and more specifically, to a preparation process of an amine liquid purification resin for a carbon capture system. Background Art
[0002] Amine liquid, as a commonly used chemical absorbent in carbon capture systems, will produce byproducts such as heat-stable salts during long-term contact with complex components in flue gas (such as oxygen, carbon dioxide, sulfur dioxide, nitrogen oxides, etc.). Especially in the process of carbon capture of flue gas produced by the combustion of high-sulfur coal, due to the relatively high sulfur dioxide content in the flue gas, a large amount of high-valent heat-stable salts such as sulfates will be generated.
[0003] The continuous increase in the concentration of heat-stable salts will have many negative effects on the carbon capture system. On the one hand, the carbon capture efficiency will be significantly reduced; on the other hand, some heat-stable salts with strong acidity and chelating effects on metals will accelerate the corrosion of equipment, shorten the service life of equipment, and increase maintenance costs.
[0004] In order to solve the problem caused by the accumulation of heat-stable salts, ion exchange technology is usually used. Among the many purification equipment, most of them choose functional styrene ion exchange resins. This type of resin is polymerized by styrene and divinylbenzene. The unique benzene ring and cross-linking structure give it good stability and mechanical strength, but its pores are relatively narrow and fixed. When facing certain high-valent complex anions, the diffusion and exchange of ions inside the resin are restricted, resulting in poor exchange effect, which in turn affects the overall heat-stable salt removal rate.
[0005] The patent application document with publication number CN104725541A discloses a method for preparing an ion exchange resin for removing heat-stable salts from an alcohol amine solution, comprising adding styrene, divinylbenzene, etc. into a polymerization kettle for polymerization reaction to obtain polystyrene white balls, which are then chloromethylated and reacted with trimethylamine to obtain fine particle resin.
[0006] The fine particle resin in the patent application document has a pore structure that is formed only by the polymerization and cross-linking process of the polymer itself. This pore structure often has a small pore size and is difficult to control, while heat-stable salts often contain a variety of high-valent anions. The smaller pore size hinders the diffusion and entry of high-valent anions into the internal pores of the resin, resulting in the inability to fully carry out the ion exchange process and difficulty in achieving the ideal exchange effect, thereby affecting the overall removal rate of heat-stable salts in the amine solution. Summary of the invention
[0007] In order to improve the removal rate of heat-stable salts in amine solution, the present application provides a preparation process of amine solution purification resin for carbon capture system.
[0008] The present application provides a preparation process for amine liquid purification resin for carbon capture system, which adopts the following technical scheme: A process for preparing an amine liquid purification resin for a carbon capture system comprises the following steps: S1: Styrene, divinylbenzene, acrylate, initiator, porogen, dispersant and water are mixed evenly, heated to 65-100°C, polymerized for 4-8 hours, cooled, solid-liquid separated, porogen extracted, washed and dried to obtain polystyrene microspheres; S2: uniformly mix polystyrene microspheres, chloromethyl methyl ether, Lewis acid catalyst and solvent, heat to 30-50°C, react for 6-8h, cool, separate solid from liquid, wash and dry to obtain chloromethylated polystyrene microspheres; S3: uniformly mix chloromethylated polystyrene microspheres, triethylenetetramine, tetrabutylammonium bromide, antioxidant and ethanol, heat to 80-100°C, react for 10-20 hours, cool, separate solid from liquid, wash, dry, and after plasma treatment, immerse in a silane coupling agent solution with a pH of 8-10 for 2-4 hours, separate solid from liquid, wash, and dry to obtain a purification resin; The mass ratio of styrene, divinylbenzene, acrylate and porogen is 1:(0.1-0.3):(0.1-0.15):(1-1.5); the porogen includes hyperbranched polyamide and dodecane.
[0009] By adopting the above technical scheme, first, when acrylate is copolymerized with styrene and divinylbenzene, acrylate can participate in the formation of a more uniform and stable cross-linked network structure. Divinylbenzene, as a cross-linking agent, can form a chemical bond connection between the molecular chains of styrene and acrylate. The reactivity and structural characteristics of acrylate enable it to play a better regulatory role in the cross-linked network, making the cross-linked network more dense and uniform. Its uniform cross-linked network can more effectively disperse stress and improve the overall mechanical properties of the microspheres. The porogen hyperbranched polyamide and dodecane form abundant nanoscale pores during the polymerization process, increasing the specific surface area of the polystyrene microspheres; the addition of dodecane further adjusts the size and distribution of the pores, so that the resin has an ideal specific surface area and pore size distribution. This optimized pore structure is conducive to the diffusion of heat-stable salts and improves the adsorption and exchange efficiency of the resin. Subsequent extraction treatment effectively removes the porogen and unreacted monomers to form a uniform and stable pore structure.
[0010] Secondly, under the action of Lewis acid catalyst, chloromethyl methyl ether was used to chloromethylate the polystyrene microspheres, introducing chloromethyl groups on the benzene rings, providing active sites for subsequent functionalization.
[0011] Finally, the chloromethylated polystyrene microspheres reacted with triethylenetetramine and tetrabutylammonium bromide, and the amino groups of the organic amines were introduced to the surface of the polystyrene microspheres. Tetrabutylammonium bromide, as a phase transfer catalyst, can promote the transfer of organic amines from the solvent phase to the resin surface, accelerate the reaction rate, and make the reaction more fully proceed. This not only improves the efficiency of the amination reaction, but also ensures the uniform distribution of functional groups on the resin surface, which is beneficial to improve the overall adsorption performance and stability of the resin. Afterwards, oxygen-containing functional groups (such as hydroxyl groups, carboxyl groups, etc.) are introduced to the resin surface through plasma treatment to increase the surface activity and roughness. These active groups can chemically bond with silane coupling agents to increase the bonding strength and coverage of silane coupling agents on the resin surface. The introduction of silane coupling agents further enhances the surface chemical activity of the resin, optimizes the adsorption conditions, and improves the selectivity and efficiency of adsorption.
[0012] Preferably, the mass ratio of the polystyrene microspheres, chloromethyl methyl ether and Lewis acid catalyst is 1:(2-4):(0.1-0.2); Preferably, the mass ratio of the chloromethylated polystyrene microspheres to triethylenetetramine and tetrabutylammonium bromide is 1:(1-3):(0.008-0.02).
[0013] Preferably, the solvent is dichloromethane.
[0014] Preferably, the mass ratio of the hyperbranched polyamide to dodecane is (1-3):(1-2).
[0015] Preferably, in step S1, the initiator is benzoyl peroxide, and the amount of benzoyl peroxide is 1% to 2.5% of the total mass of styrene, divinylbenzene and acrylate.
[0016] Preferably, the acrylate is any one of methyl methacrylate and ethyl methacrylate.
[0017] Preferably, the Lewis acid catalyst is aluminum chloride.
[0018] Preferably, the dispersant is any one of polyvinyl alcohol and gelatin, and the amount of the dispersant in water is (4-8) g / L.
[0019] Preferably, the power of the plasma treatment is 50-100 W, and the treatment time is 5-15 min.
[0020] Preferably, the antioxidant is antioxidant 2246, and the amount of antioxidant 2246 used is 0.5% to 2% of the mass of triethylenetetramine.
[0021] Preferably, in step S3, when adding triethylenetetramine, the step of adding triethylamine is also included, and the amount of triethylamine used is 10% to 30% of the mass of triethylenetetramine.
[0022] Preferably, the silane coupling agent solution comprises 3-aminopropyltriethoxysilane, ethanol and water, the mass fraction of the silane coupling agent solution is 4% to 6%, and the mass fraction of the ethanol is 20% to 40%.
[0023] Preferably, in step S1, when adding styrene, the step of adding ion-imprinted polymer A is also included. The preparation method of the ion-imprinted polymer A comprises the following steps: after uniformly mixing sodium sulfate, methacrylic acid and acetonitrile aqueous solution, adding ethylene glycol dimethacrylate and azobisisobutyronitrile in an inert atmosphere and uniformly mixing, heating to 60-80° C., reacting for 12-24 hours, cooling, solid-liquid separation, washing, crushing, acid eluting, washing, and drying to obtain the ion-imprinted polymer A; The molar ratio of sodium sulfate to methacrylic acid is 1:(1.5-2.5); the molar ratio of ethylene glycol dimethacrylate to methacrylic acid is (3-5):1; and the amount of the ion-imprinted polymer A is 10%-20% of the mass of styrene.
[0024] Preferably, the amount of azobisisobutyronitrile used is 1% to 2% of the total mass of methacrylic acid and ethylene glycol dimethacrylate.
[0025] Preferably, the particle size distribution of the ion-imprinted polymer A is 10-100 μm.
[0026] Preferably, in step S1, when adding styrene, the step of adding ion imprinting polymer B is also included; The preparation method of the ion-imprinted polymer B comprises the following steps: after sodium carbonate, acrylic acid and water are uniformly mixed, pentaerythritol tetraacrylate and an oxidation-reduction initiator are added and mixed uniformly under an inert atmosphere, the temperature is raised to 60-80° C., reacted for 6-8 hours, cooled, solid-liquid separation, washing, crushing, acid elution, washing, and drying to obtain the ion-imprinted polymer B; The molar ratio of sodium carbonate to acrylic acid is 1:(2-3); the molar ratio of pentaerythritol tetraacrylate to acrylic acid is (1-2):1; and the amount of the ion-imprinted polymer B is 5%-10% of the mass of styrene.
[0027] Preferably, the redox initiator comprises potassium persulfate and sodium bisulfite, and the mass ratio of potassium persulfate to sodium sulfite is 1:(0.5~1).
[0028] Preferably, the amount of the redox initiator is 1% to 3% of the total mass of acrylic acid and pentaerythritol tetraacrylate.
[0029] Preferably, the particle size distribution of the ion-imprinted polymer B is 10-100 μm.
[0030] By adopting the above technical solution and adding ion-imprinted polymer A or B, the final prepared amine solution purification resin has the specific recognition ability for sulfate ions or carbonate ions. Ion-imprinted polymers are formed by polymerizing template ions (such as sulfate or carbonate) with functional monomers and then removing the template ions. Their surfaces have specific recognition sites that match the shape and chemical properties of the template ions. These sites can quickly capture sulfate ions or carbonate ions through mechanisms such as hydrogen bonds and electrostatic interactions, significantly improving the selective adsorption performance of the resin for specific heat-stable salt ions, thereby more effectively removing sulfate ion or carbonate ion impurities in the amine solution and improving the purity of the amine solution.
[0031] Ion-imprinted polymer A or B is combined with polystyrene and other polymers through covalent bonds or strong physical effects and is evenly dispersed in the resin matrix. This combination method not only ensures the stability of the ion-imprinted polymer, but also enhances the mechanical strength of the resin, so that it can better withstand the impact and pressure of the fluid during the amine liquid purification process and prolong its service life.
[0032] In addition, due to the specific adsorption of sulfate ions or carbonate ions by ion-imprinted polymer A or B, the regeneration process can be achieved by selective elution (such as using a low-concentration alkaline solution). This targeted regeneration not only improves the regeneration efficiency, but also reduces the amount of eluent used and reduces the operating cost.
[0033] Preferably, in step S1, after the polymerization reaction starts, a step of adding modified chitosan is further included. The preparation method of the modified chitosan comprises the following steps: Under an inert atmosphere, chitosan is dissolved in a dilute acetic acid solution, cooled to 0-5°C, acetic anhydride is added, reacted for 4-6 hours, neutralized, solid-liquid separated, washed, dried, added to N,N-dimethylformamide, and then pyridine and trimethylsilyl chloride are added and mixed evenly, reacted at 20-30°C for 2-4 hours, solid-liquid separated, washed, and dried to obtain modified chitosan; The mass ratio of chitosan, acetic anhydride, pyridine and trimethylchlorosilane is 10: (1.5-2.5): (0.75-1): (0.9-1.2); the amount of modified chitosan is 4%-8% of the mass of styrene.
[0034] Preferably, the mass fraction of the dilute acetic acid solution is 2% to 4%.
[0035] Preferably, the chitosan has a deacetylation degree of 70% to 80% and a molecular weight distribution of 80,000 to 100,000.
[0036] By adopting the above technical solution, modified chitosan is added in the middle of the polymerization reaction. At this time, some polystyrene segments have been formed in the system. The small amount of amino groups remaining on the modified chitosan molecular chain can interact with the polymer segments to promote chain growth and cross-linking. The rigid skeleton of the modified chitosan can also provide physical support and optimize the pore structure of the microspheres. At the same time, its surface active groups promote the formation of a cross-linked network. In the subsequent process, the protective groups of the modified chitosan can be selectively hydrolyzed by controlling the acidic or alkaline conditions. This controllable hydrolysis can dynamically adjust the adsorption site density of the resin and balance the adsorption capacity and regeneration performance.
[0037] The rigid skeleton structure of the modified chitosan synergizes with the porogen during the polymerization process to form a hierarchical pore structure (micropore-mesopore), which increases the specific surface area and provides more adsorption sites for heat-stable salt ions, thereby enhancing the adsorption effect on heat-stable salts.
[0038] Preferably, in step S1, when adding divinylbenzene, the step of adding triallyl isocyanurate is also included, and the amount of triallyl isocyanurate is 3% to 6% of the mass of styrene.
[0039] By adopting the above technical solution, the addition of triallyl isocyanurate makes the network structure of polystyrene microspheres more complex and diversified. This complex network structure helps to improve the mechanical properties and thermal stability of polystyrene microspheres, so that they can maintain good morphology and performance under different environmental conditions. At the same time, during the polymerization process, the presence of triallyl isocyanurate can affect the dispersion and effect of the porogen, thereby affecting the pore structure of the microspheres. The appropriate amount of triallyl isocyanurate can make the microspheres form a more uniform and richer pore structure, increase the specific surface area of the microspheres, and improve the adsorption capacity and loading capacity of the subsequent purification resin for the target substance.
[0040] In summary, this application has the following beneficial effects: 1. This application uses styrene as the main monomer, and divinylbenzene and diallylamine as auxiliary monomers to synthesize a three-dimensional network polymer with certain mechanical strength and flexibility. At the same time, hyperbranched polyamide and dodecane are used as a composite porogen to form pores of specific size and distribution inside the resin. After the polymerization reaction is completed, the porogen is removed, and then chloromethylation and amination treatment are carried out, which greatly improves the adsorption efficiency and adsorption capacity of the purification resin.
[0041] 2. The present application preferably adds ion-imprinted polymer A or B when synthesizing polystyrene microspheres, thereby improving the selective adsorption performance of specific heat-stable salt ions, and at the same time increasing the adsorption capacity of the purification resin for sulfate ions or carbonate ions, so that the purification resin can adsorb more sulfate ions or carbonate ions per unit mass or volume, thereby improving the removal rate of heat-stable salts in the amine solution.
[0042] 3. The present application preferably adds modified chitosan in the middle stage of the synthesis of polystyrene microspheres, enriching the heat-stable salt adsorption sites of the subsequent purification resin, improving the adsorption capacity and adsorption efficiency of the purification resin, and ultimately improving the removal rate of the purification resin for heat-stable salts. DETAILED DESCRIPTION
[0043] The present application is further described in detail below with reference to embodiments.
[0044] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0045] The hyperbranched polyamide is an amino-terminated hyperbranched polyamide with a molecular weight distribution of 350-2200 and a purity of 99%, purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd. Linear polyamide was purchased from Suzhou Huida Plastics Import and Export Co., Ltd.
[0046] Preparation Examples 1-3 Ion Imprinted Polymer A Preparation Example 1 This preparation example provides a method for preparing an ion-imprinted polymer A, comprising the following steps: 0.1 mol of sodium sulfate and 0.15 mol of methacrylic acid were added to the reactor, and then a mixed solvent consisting of 140 ml of acetonitrile and 60 ml of deionized water was added, and the mixture was stirred and mixed evenly. Under a nitrogen atmosphere, 0.45 mol of ethylene glycol dimethacrylate and azobisisobutyronitrile were added and stirred and mixed evenly. The temperature was raised to 60°C, and the reaction was carried out for 24 hours. The mixture was naturally cooled to room temperature, filtered, and washed with acetonitrile for 3 times. The product was crushed until it was completely passed through a 200-mesh sieve, and then passed through a 1250-mesh sieve to take the sieve. , transfer the material on the sieve to an acid elution container, add 550 ml of 0.2 mol / L hydrochloric acid solution, and perform acid elution at room temperature with a stirring speed of 200 rpm. Take a small amount of eluate to detect the sulfate ion concentration every 1 hour. When the sulfate ion concentration changes by less than 5% for two consecutive tests, stop eluting, then filter, wash with a large amount of deionized water until neutral, then transfer to a vacuum drying oven at 40°C, dry for 4 hours, then heat to 60°C, and dry to constant weight to obtain ion imprinted polymer A.
[0047] The amount of azobisisobutyronitrile used is 2% of the total mass of methacrylic acid and ethylene glycol dimethacrylate, which is about 2.1 g.
[0048] Preparation Example 2 0.1 mol of sodium sulfate and 0.25 mol of methacrylic acid were added to the reactor, and then a mixed solvent consisting of 280 ml of acetonitrile and 120 ml of deionized water was added, and the mixture was stirred and mixed evenly. Under a nitrogen atmosphere, 1.25 mol of ethylene glycol dimethacrylate and azobisisobutyronitrile were added and stirred and mixed evenly. The temperature was raised to 80°C, and the reaction was carried out for 12 hours. The mixture was naturally cooled to room temperature, filtered, and washed with acetonitrile for 3 times. The product was crushed until it was completely passed through a 200-mesh sieve, and then passed through a 1250-mesh sieve to take the sieve. , transfer the material on the sieve to an acid elution container, add 600 ml of 0.2 mol / L hydrochloric acid solution, and perform acid elution at room temperature with a stirring speed of 200 rpm. Take a small amount of eluate to detect the sulfate ion concentration every 1 hour. When the sulfate ion concentration changes by less than 5% for two consecutive tests, stop eluting, then filter, wash with a large amount of deionized water until neutral, then transfer to a vacuum drying oven at 40°C, dry for 4 hours, then heat to 60°C, and dry to constant weight to obtain ion-imprinted polymer A.
[0049] The amount of azobisisobutyronitrile used is 1% of the total mass of methacrylic acid and ethylene glycol dimethacrylate, which is about 2.7 g.
[0050] Preparation Example 3 0.1 mol of sodium sulfate and 0.2 mol of methacrylic acid were added to the reactor, and then a mixed solvent consisting of 210 ml of acetonitrile and 90 ml of deionized water was added, and the mixture was stirred and mixed evenly. Under a nitrogen atmosphere, 0.8 mol of ethylene glycol dimethacrylate and azobisisobutyronitrile were added and stirred and mixed evenly. The temperature was raised to 70°C, and the reaction was carried out for 18 hours. The mixture was naturally cooled to room temperature, filtered, and washed with acetonitrile for 3 times. The product was crushed until it was completely passed through a 200-mesh sieve, and then passed through a 1250-mesh sieve to obtain the sieve. The material on the sieve was transferred to an acid elution container, and 570 ml of 0.2 mol / L hydrochloric acid solution was added. The acid elution was performed at room temperature with a stirring speed of 200 rpm. A small amount of eluate was taken every 1 hour to detect the sulfate ion concentration. When the sulfate ion concentration changed by less than 5% for two consecutive tests, the elution was stopped, and then filtered, washed with a large amount of deionized water until neutral, and then transferred to a vacuum drying oven at 40°C, dried for 4 hours, and then heated to 60°C and dried to constant weight to obtain ion-imprinted polymer A.
[0051] The amount of azobisisobutyronitrile used is 1.5% of the total mass of methacrylic acid and ethylene glycol dimethacrylate, which is about 2.6 g.
[0052] Preparation Examples 4-6 Ion Imprinted Polymer B Preparation Example 4 This preparation example provides a method for preparing an ion-imprinted polymer B, comprising the following steps: 0.1 mol of sodium carbonate and 0.2 mol of acrylic acid were added into the reactor, and then 300 ml of deionized water was added and stirred to mix evenly. Under a nitrogen atmosphere, 0.2 mol of pentaerythritol tetraacrylate and an oxidation-reduction initiator were added and stirred to mix evenly. The temperature was raised to 60°C, and the reaction was carried out for 8 hours. The mixture was naturally cooled to room temperature, filtered, and washed with deionized water for 3 times. The product was crushed until it was completely passed through a 200-mesh sieve, and then passed through a 1250-mesh sieve to take the sieve-surface material. The sieve-surface material was transferred to an acid elution container, and 550 ml of 0.2 mol / L hydrochloric acid solution was added. The acid elution was carried out at a stirring speed of 200 rpm at room temperature. A small amount of the eluate was taken to detect the carbonate ion concentration every 1 hour. When the carbonate ion concentration changed by less than 5% for two consecutive times, the elution was stopped, and then filtered, and the mixture was washed with a large amount of deionized water until it was neutral. The mixture was then transferred into a vacuum drying oven at 40°C and dried for 4 hours. The mixture was then heated to 60°C and dried to constant weight to obtain an ion-imprinted polymer B.
[0053] The amount of the redox initiator used is 3% of the total mass of acrylic acid and pentaerythritol tetraacrylate, and the redox initiator includes 1.70 g of potassium persulfate and 0.85 g of sodium bisulfite.
[0054] Preparation Example 5 This preparation example provides a method for preparing an ion-imprinted polymer B, comprising the following steps: 0.1 mol of sodium carbonate and 0.3 mol of acrylic acid were added into the reactor, and then 600 ml of deionized water was added and stirred to mix evenly. Under a nitrogen atmosphere, 0.6 mol of pentaerythritol tetraacrylate and an oxidation-reduction initiator were added and stirred to mix evenly. The temperature was raised to 80°C, and the mixture was reacted for 6 hours. The mixture was naturally cooled to room temperature, filtered, and washed with deionized water for 3 times. The product was crushed until it was completely passed through a 200-mesh sieve, and then passed through a 1250-mesh sieve to take the sieve-surface material. The sieve-surface material was transferred to an acid elution container, and 600 ml of 0.2 mol / L hydrochloric acid solution was added. The acid elution was carried out at a stirring speed of 200 rpm at room temperature. A small amount of the eluate was taken every 1 hour to detect the carbonate ion concentration. When the carbonate ion concentration changed by less than 5% for two consecutive times, the elution was stopped, and then filtered, and the mixture was washed with a large amount of deionized water until it was neutral. The mixture was then transferred into a vacuum drying oven at 40°C and dried for 4 hours. The mixture was then heated to 60°C and dried to constant weight to obtain an ion-imprinted polymer B.
[0055] The amount of the redox initiator used is 1% of the total mass of acrylic acid and pentaerythritol tetraacrylate, and the redox initiator includes 1.33 g of potassium persulfate and 1.0 g of sodium bisulfite.
[0056] Preparation Example 6 This preparation example provides a method for preparing an ion-imprinted polymer B, comprising the following steps: 0.1 mol of sodium carbonate and 0.25 mol of acrylic acid were added into the reactor, and then 500 ml of deionized water was added and stirred to mix evenly. Under a nitrogen atmosphere, 0.375 mol of pentaerythritol tetraacrylate and an oxidation-reduction initiator were added and stirred to mix evenly. The temperature was raised to 70°C, and the reaction was carried out for 7 hours. The mixture was naturally cooled to room temperature, filtered, and washed with deionized water for 3 times. The product was crushed until it was completely passed through a 200-mesh sieve, and then passed through a 1250-mesh sieve to take the sieve-surface material. The sieve-surface material was transferred to an acid elution container, and 570 ml of 0.2 mol / L hydrochloric acid solution was added. The acid elution was carried out at a stirring speed of 200 rpm at room temperature. A small amount of the eluate was taken to detect the carbonate ion concentration every 1 hour. When the carbonate ion concentration changed by less than 5% for two consecutive times, the elution was stopped, and then filtered, and the mixture was washed with a large amount of deionized water until it was neutral. The mixture was then transferred into a vacuum drying oven at 40°C and dried for 4 hours. The mixture was then heated to 60°C and dried to constant weight to obtain an ion-imprinted polymer B.
[0057] The amount of the redox initiator used is 2% of the total mass of acrylic acid and pentaerythritol tetraacrylate, and the redox initiator includes 1.94 g of potassium persulfate and 1.94 g of sodium bisulfite.
[0058] Preparation Examples 7-9 Modified Chitosan Preparation Example 7 This preparation example provides a method for preparing modified chitosan, comprising the following steps: Under a nitrogen atmosphere, 20 g of chitosan and 100 g of 2% dilute acetic acid were added to a reactor and stirred until the chitosan was completely dissolved. The mixture was transferred to an ice-salt bath and the temperature was maintained between 0 and 5°C. 3 g of acetic anhydride was slowly added and reacted for 4 h. The pH was adjusted to neutral with 5% ammonia water, centrifuged, washed 3 times with deionized water, dried to constant weight at 50°C, and then added to 150 g of N,N-dimethylformamide and stirred to mix evenly. Then, 1.5 g of pyridine and 1.8 g of trimethylchlorosilane were added and stirred to mix evenly. After reacting for 4 h at 20°C, methanol was added until no precipitation occurred. The mixture was filtered, rinsed 3 times with anhydrous ethanol, and transferred to a vacuum drying oven at 50°C and dried to constant weight to obtain modified chitosan.
[0059] Among them, the deacetylation degree of chitosan is 70%~80%, and the molecular weight distribution is 80000~100000.
[0060] Preparation Example 8 This preparation example provides a method for preparing modified chitosan, comprising the following steps: Under a nitrogen atmosphere, 20 g of chitosan and 100 g of 3% dilute acetic acid were added to a reactor and stirred until the chitosan was completely dissolved. The mixture was transferred to an ice-salt bath and the temperature was maintained between 0 and 5°C. 5 g of acetic anhydride was slowly added and reacted for 5 h. The pH was adjusted to neutral with 5% ammonia water, centrifuged, washed 3 times with deionized water, dried to constant weight at 50°C, and then added to 150 g of N,N-dimethylformamide and stirred to mix evenly. Then, 2 g of pyridine and 2.4 g of trimethylchlorosilane were added and stirred to mix evenly. After reacting for 2 h at 30°C, methanol was added until no precipitation occurred. The mixture was filtered, rinsed 3 times with anhydrous ethanol, and transferred to a vacuum drying oven at 50°C and dried to constant weight to obtain modified chitosan.
[0061] Among them, the deacetylation degree of chitosan is 70%~80%, and the molecular weight distribution is 80000~100000.
[0062] Preparation Example 9 This preparation example provides a method for preparing modified chitosan, comprising the following steps: Under a nitrogen atmosphere, 20 g of chitosan and 100 g of 4% dilute acetic acid were added to a reactor and stirred until the chitosan was completely dissolved. The mixture was transferred to an ice-salt bath and the temperature was maintained between 0 and 5°C. 4 g of acetic anhydride was slowly added and reacted for 6 h. The pH was adjusted to neutral with 5% ammonia water, centrifuged, washed 3 times with deionized water, dried to constant weight at 50°C, and then added to 150 g of N,N-dimethylformamide and stirred to mix evenly. Then, 1.8 g of pyridine and 2.2 g of trimethylchlorosilane were added and stirred to mix evenly. After reacting for 3.5 h at 25°C, methanol was added until no precipitation occurred. The mixture was filtered, rinsed 3 times with anhydrous ethanol, and transferred to a vacuum drying oven at 50°C and dried to constant weight to obtain modified chitosan.
[0063] Among them, the deacetylation degree of chitosan is 70%~80%, and the molecular weight distribution is 80000~100000.
[0064] Example 1 This embodiment provides a preparation process for an amine liquid purification resin for a carbon capture system, comprising the following steps: S1: 100 g of styrene, 10 g of divinylbenzene, 10 g of ethyl methacrylate, 3 g of benzoyl peroxide, 50 g of amino-terminated hyperbranched polyamide and 50 g of dodecane were mixed evenly to obtain an organic phase; 4 g of polyvinyl alcohol and 1000 ml of deionized water were mixed evenly to obtain an aqueous phase; the organic phase was slowly added dropwise to the aqueous phase, and stirring was continued at a speed of 200 rpm. After the addition was completed, the temperature was raised to 65° C., the polymerization reaction was carried out for 8 hours, and the mixture was naturally cooled to room temperature, vacuum filtered, and the filter cake was collected; The filter cake was then immersed in a container filled with petroleum ether, and the ultrasonic device was turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 20 min, and vacuum filtration was performed; then, the filter cake was immersed in a new container filled with petroleum ether again, and the ultrasonic device was turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 20 min, and vacuum filtration was performed; The filter cake treated with petroleum ether was immersed in a container filled with N,N-dimethylformamide, and the ultrasonic device was also turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 20 minutes, and vacuum filtration was performed. Then, it was immersed in a new container filled with N,N-dimethylformamide again, and the ultrasonic device was also turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 20 minutes, and vacuum filtration was performed. Then, the mixture was washed with deionized water for three times, vacuum filtered, and then placed in a vacuum drying oven and dried at 40°C to a constant weight to obtain polystyrene microspheres. S2: 100 g of polystyrene microspheres and 300 ml of dichloromethane were stirred and mixed in a reactor, and then 200 g of chloromethyl methyl ether was added and stirred and mixed, and then aluminum chloride was added in 5 times, with an interval of 10-15 min each time, and the amount added each time was 2 g, and the reaction temperature was controlled to be 30°C. After stirring and reacting for 8 hours, it was naturally cooled to room temperature, neutralized with a 5% ammonia aqueous solution, and the organic phase was taken out after standing and stratified, washed with deionized water until neutral, vacuum filtered, and transferred to a vacuum drying oven, and dried to constant weight at 40°C to obtain chloromethylated polystyrene microspheres; S3: 100 g of chloromethylated polystyrene microspheres, 100 g of triethylenetetramine, 0.8 g of tetrabutylammonium bromide, 0.5 g of antioxidant 2246 and 500 ml of ethanol were stirred and mixed evenly, heated to 80°C, reacted for 20 hours, naturally cooled to room temperature, vacuum filtered, washed twice with ethanol, transferred to a vacuum drying oven, dried to constant weight at 40°C, and then evenly spread on the sample stage of the plasma treatment equipment, with a nitrogen flow rate of 30 sccm and a power of 50 W for 15 minutes, and then immersed in a prepared 3-aminopropyltriethoxysilane solution with a pH value between 8 and 8.5 and a mass fraction of 4%, soaked for 4 hours, vacuum filtered, washed twice with ethanol, transferred to a vacuum drying oven, and dried to constant weight at 40°C to obtain a purified resin.
[0065] The 3-aminopropyltriethoxysilane solution includes 3-aminopropyltriethoxysilane, ethanol and water, and the mass fraction of ethanol is 20%.
[0066] Example 2 S1: 100 g of styrene, 30 g of divinylbenzene, 15 g of methyl methacrylate, 1.45 g of benzoyl peroxide, 90 g of terminal amino hyperbranched polyamide and 60 g of dodecane were mixed evenly to obtain an organic phase; 8 g of gelatin and 1000 ml of deionized water were mixed evenly to obtain an aqueous phase; the organic phase was slowly added dropwise to the aqueous phase, and stirring was continued at a speed of 200 rpm. After the addition was completed, the temperature was raised to 100°C, the polymerization reaction was carried out for 4 hours, and the mixture was naturally cooled to room temperature, vacuum filtered, and the filter cake was collected; The filter cake was then immersed in a container filled with petroleum ether, and the ultrasonic device was turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 30 min, and vacuum filtration was performed; then, the filter cake was immersed in a new container filled with petroleum ether again, and the ultrasonic device was turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 30 min, and vacuum filtration was performed; The filter cake treated with petroleum ether was immersed in a container filled with N,N-dimethylformamide, and the ultrasonic device was also turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 30 minutes, and vacuum filtration was performed; then, it was immersed again in a new container filled with N,N-dimethylformamide, and the ultrasonic device was also turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 30 minutes, and vacuum filtration was performed; Then, the mixture was washed with deionizer for 3 times, vacuum filtered, and then placed in a vacuum drying oven and dried at 40°C to a constant weight to obtain polystyrene microspheres. S2: 100 g of polystyrene microspheres and 300 ml of dichloromethane were stirred and mixed in a reactor, and then 400 g of chloromethyl methyl ether was added and stirred and mixed, and then aluminum chloride was added in 5 times, with an interval of 10-15 min between each addition and an amount of 4 g each time, and the reaction temperature was controlled to be 50°C. After stirring and reacting for 6 hours, the mixture was naturally cooled to room temperature, neutralized with a 5% ammonia aqueous solution, allowed to stand and decomposed, and the organic phase was taken, washed with deionized water until neutral, vacuum filtered, and transferred to a vacuum drying oven, and dried to constant weight at 40°C to obtain chloromethylated polystyrene microspheres; S3: 100 g of chloromethylated polystyrene microspheres, 300 g of triethylenetetramine, 30 g of triethylamine, 2 g of tetrabutylammonium bromide, 2 g of antioxidant 2246 and 500 ml of ethanol were stirred and mixed evenly, heated to 100°C, reacted for 10 h, naturally cooled to room temperature, vacuum filtered, washed twice with ethanol, transferred to a vacuum drying oven, dried to constant weight at 40°C, and then evenly spread on the sample stage of the plasma treatment equipment, with a nitrogen flow rate of 30 sccm and a power of 100 W for 5 min, and then immersed in a prepared 3-aminopropyltriethoxysilane solution with a pH value between 9.5 and 10 and a mass fraction of 6%, soaked for 2 h, vacuum filtered, washed twice with ethanol, transferred to a vacuum drying oven, dried to constant weight at 40°C to obtain a purified resin.
[0067] The 3-aminopropyltriethoxysilane solution includes 3-aminopropyltriethoxysilane, ethanol and water, and the mass fraction of ethanol is 40%.
[0068] Example 3 S1: 100 g of styrene, 20 g of divinylbenzene, 12 g of methyl methacrylate, 2.6 g of benzoyl peroxide, 80 g of terminal amino hyperbranched polyamide and 60 g of dodecane were mixed evenly to obtain an organic phase; 6 g of polyvinyl alcohol and 1000 ml of deionized water were mixed evenly to obtain an aqueous phase; the organic phase was slowly added dropwise to the aqueous phase, and stirring was continued at a speed of 200 rpm. After the addition was completed, the temperature was raised to 85°C, the polymerization reaction was carried out for 6 hours, and the mixture was naturally cooled to room temperature, vacuum filtered, and the filter cake was collected; The filter cake was then immersed in a container filled with petroleum ether, and the ultrasonic device was turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 25 min, and vacuum filtration was performed; then, the filter cake was immersed in a new container filled with petroleum ether again, and the ultrasonic device was turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 25 min, and vacuum filtration was performed; The filter cake treated with petroleum ether was immersed in a container filled with N,N-dimethylformamide, and the ultrasonic equipment was also turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 25 minutes, and vacuum filtration was performed; then immersed in a new container filled with N,N-dimethylformamide, and the ultrasonic equipment was also turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 25 minutes, and vacuum filtration was performed; Then, the mixture was washed with deionized water for three times, vacuum filtered, and then placed in a vacuum drying oven and dried at 40°C to a constant weight to obtain polystyrene microspheres. S2: 100 g of polystyrene microspheres and 300 ml of dichloromethane were stirred and mixed in a reactor, and then 300 g of chloromethyl methyl ether was added and stirred and mixed, and then aluminum chloride was added in 5 times, with an interval of 10-15 min between each addition and an amount of 3 g each time, and the reaction temperature was controlled to be 40°C. After stirring and reacting for 7 hours, the mixture was naturally cooled to room temperature, neutralized with a 5% ammonia aqueous solution, and the organic phase was taken out after standing and stratified, washed with deionized water until neutral, vacuum filtered, and transferred to a vacuum drying oven, and dried to constant weight at 40°C to obtain chloromethylated polystyrene microspheres; S3: 100 g of chloromethylated polystyrene microspheres, 200 g of triethylenetetramine, 60 g of triethylamine, 1.2 g of tetrabutylammonium bromide, 1.5 g of antioxidant 2246 and 500 ml of ethanol were stirred and mixed evenly, heated to 90°C, reacted for 16 hours, naturally cooled to room temperature, vacuum filtered, washed twice with ethanol, transferred to a vacuum drying oven, dried to constant weight at 40°C, and then evenly spread on the sample stage of the plasma treatment equipment, with a nitrogen flow rate of 30 sccm and a power of 100 W for 10 minutes, and then immersed in a prepared 3-aminopropyltriethoxysilane solution with a mass fraction of 5% and a pH between 8.5 and 9.5, soaked for 3 hours, vacuum filtered, washed twice with ethanol, transferred to a vacuum drying oven, and dried to constant weight at 40°C to obtain a purification resin.
[0069] The 3-aminopropyltriethoxysilane solution includes 3-aminopropyltriethoxysilane, ethanol and water, and the mass fraction of ethanol is 30%.
[0070] Example 4 The difference between this embodiment and embodiment 3 is that: In step S1, when styrene was added, 10 g of ion-imprinted polymer A was also added; In step S3, the amount of triethylamine is 40g; Ion-imprinted polymer A is from Preparation Example 1.
[0071] The rest is the same as in Example 3.
[0072] Example 5 The difference between this embodiment and embodiment 4 is that: In step S1, when styrene was added, 15 g of ion-imprinted polymer A was also added; Ion-imprinted polymer A is from Preparation Example 2.
[0073] The rest is the same as Example 4.
[0074] Example 6 The difference between this embodiment and embodiment 5 is that: In step S1, when styrene is added, 15 g of ion-imprinted polymer A and 5 g of ion-imprinted polymer B are also added; Ion-imprinted polymer A is from Preparation Example 3; ion-imprinted polymer B is from Preparation Example 4.
[0075] The rest is the same as Example 5.
[0076] Example 7 The difference between this embodiment and embodiment 6 is that: In step S1, when styrene is added, 15 g of ion imprinted polymer A and 10 g of ion imprinted polymer B are also added; Ion-imprinted polymer A is from Preparation Example 3; ion-imprinted polymer B is from Preparation Example 5.
[0077] The rest is the same as Example 6.
[0078] Example 8 The difference between this embodiment and embodiment 7 is that: S1: 100 g of styrene, 15 g of ion-imprinted polymer A, 10 g of ion-imprinted polymer B, 20 g of divinylbenzene, 12 g of methyl methacrylate, 2.6 g of benzoyl peroxide, 80 g of amino-terminated hyperbranched polyamide and 60 g of dodecane were mixed uniformly to obtain an organic phase; 6 g of polyvinyl alcohol and 1000 ml of deionized water were mixed uniformly to obtain an aqueous phase; the organic phase was slowly added dropwise to the aqueous phase, and the mixture was continuously stirred at a speed of 200 rpm. After the addition was completed, the temperature was raised to 85° C., and when the polymerization reaction was carried out for 3 h, 4 g of modified chitosan was added, and the temperature was maintained at 85° C., and the reaction was continued for 3 h, and then the mixture was naturally cooled to room temperature, vacuum filtered, and the filter cake was collected; Then, the filter cake was immersed in a container filled with petroleum ether, and the ultrasonic device was turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, stirring was continued for 25 min, and vacuum filtration was performed; the filter cake was immersed in a new container filled with petroleum ether again, and the ultrasonic device was turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, stirring was continued for 25 min, and vacuum filtration was performed; The filter cake treated with petroleum ether was immersed in a container filled with N,N-dimethylformamide, and the ultrasonic device was turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 25 min, and vacuum filtration was performed; the filter cake was immersed in a new container filled with N,N-dimethylformamide again, and the ultrasonic device was turned on to assist stirring. The ultrasonic power was set to 200 W, the stirring speed was 200 rpm, and the stirring was continued for 25 min, and vacuum filtration was performed; Then, the mixture was washed with deionized water for three times, vacuum filtered, and then placed in a vacuum drying oven and dried at 40°C to a constant weight to obtain polystyrene microspheres. Ion-imprinted polymer A is from Preparation Example 3; ion-imprinted polymer B is from Preparation Example 6; and modified chitosan is from Preparation Example 7.
[0079] The rest is the same as Example 7.
[0080] Example 9 The difference between this embodiment and embodiment 8 is that: In step S1, the amount of modified chitosan used is 8 g, and the modified chitosan comes from Preparation Example 8.
[0081] The rest is the same as Example 8.
[0082] Example 10 The difference between this embodiment and embodiment 9 is that: In step S1, the amount of modified chitosan used is 6 g, and the modified chitosan comes from Preparation Example 9.
[0083] In step S1, when divinylbenzene is added, 3 g of triallyl isocyanurate is also added.
[0084] The rest is the same as Example 9.
[0085] Embodiment 11 The difference between this embodiment and embodiment 10 is that: In step S1, when divinylbenzene is added, 6 g of triallyl isocyanurate is also added.
[0086] The rest is the same as Example 10.
[0087] Comparative Example 1 The difference between this comparative example and Example 1 is: Using equal weight of linear polyamide to replace amino-terminated hyperbranched polyamide; The rest is the same as in Example 1.
[0088] Comparative Example 2 The difference between this comparative example and Example 1 is: No methyl methacrylate was added.
[0089] The rest is the same as in Example 1.
[0090] Comparative Example 3 The difference between this comparative example and Example 1 is: S3: Stir and mix 100 g of chloromethylated polystyrene microspheres, 300 g of triethylenetetramine, 90 g of triethylamine, 2 g of tetrabutylammonium bromide, 2 g of antioxidant 2246 and 500 ml of ethanol, heat to 100°C, react for 10 hours, cool naturally to room temperature, vacuum filter, wash twice with ethanol, transfer to a vacuum drying oven, and dry at 40°C to constant weight to obtain a purified resin.
[0091] The rest is the same as in Example 1.
[0092] Performance Testing (1) Test object: For a coal-fired plant, the amine liquid after the flue gas treatment after the combustion of high-sulfur coal was tested for the removal rate of heat-stable salts after being treated with the purification resins in Examples 1 to 11 and Comparative Examples 1 to 3.
[0093] In the flue gas treatment system, a sampling point is set on the circulation pipeline between the absorption tower and the regeneration tower, at a distance of 1 / 3 of the pipeline length from the absorption tower outlet. The amine liquid at this position can better reflect the properties of the overall amine liquid and the content of heat-stable salts. Sampling began after the coal-fired plant had been running stably for 24 hours. Samples were collected every 2 hours, 2000 mL each time, and a total of 5 times. The 5 samples collected were fully mixed to obtain a representative amine liquid sample. The collected amine liquid was filtered with a filter membrane with a pore size of 0.45 μm to avoid interference of impurities in subsequent detection and purification experiments. The amine liquid sample to be purified was obtained, with a density of about 1.13 g / cm 3 The initial mass concentration of heat-stable salt in the amine solution sample was tested by ion chromatography, and the test results are shown in Table 1.
[0094] Table 1 Detection data of initial mass concentration of heat-stable salt in amine solution
[0095] (2) Purification treatment: The amine solution sample was passed through the marked ion exchange columns filled with the purification resins prepared in Examples 1 to 11 and Comparative Examples 1 to 3 at a flow rate of 7 BV / h (bed volume / hour), and the purified amine solution flowing out of each ion exchange column was collected to ensure that there was no external contamination during the collection process. The purified amine solution was analyzed by ion chromatograph to analyze the concentration of each heat-stable salt anion. Three parallel experiments were conducted for each experiment. A newly filled ion exchange column was used for each experiment. The average value was taken as the result, and the removal rate of the heat-stable salt in the amine solution sample was calculated. The test results are shown in Table 2. Among them, the operating temperature, pressure and other parameters of each ion exchange column were recorded, and the operating conditions of all columns were kept consistent as much as possible. The temperature can be controlled at 40±2°C and the pressure can be maintained at 0.2±0.01MPa.
[0096] Table 2 Performance test data of amine liquid purification resin in Examples 1 to 11 and Comparative Examples 1 to 3
[0097] (3) Example 9 and Example 11 were filled into different ion exchange columns respectively, and the amine solution sample was purified at a flow rate of 7BV / h (bed volume / hour) and recycled 10 times. A new amine solution sample was used each time, and the ion exchange column was purified after each use and then recycled. The purification operation is as follows: 3% sodium hydroxide with a mass fraction of 3 times the volume of the purification resin in the ion exchange column was introduced for 30 minutes, and then rinsed with deionized water until neutral. The operating temperature, pressure and other parameters of each ion exchange column were recorded, and the operating conditions of all columns were kept consistent as much as possible. The temperature can be controlled at 40±2°C and the pressure is maintained at 0.2±0.01MPa. The total removal rate of heat-stable salts and the changes in the appearance of the purification resin were detected and recorded for the first and tenth times. The results are shown in Table 3.
[0098] Table 3 Performance test data of amine solution purification resin after recycling in Example 9 and Example 11
[0099] Combining the data in Tables 1 to 3, the following analysis is performed: Comprehensive analysis shows that the amine solution sample adopts the purification resin in Examples 1 to 11. After purification, the mass concentration of the total amount of heat-stable salt in the amine solution is not higher than 0.85%, SO 4 2- The mass concentration of SO is not higher than 0.24%, 3 2- The mass concentration of S is not higher than 0.20%. 2 O 3 2- The mass concentration of CO is not higher than 0.07%. 3 2- The mass concentration content is not higher than 0.14%.
[0100] It can be seen from Example 1 and Comparative Examples 1 to 3 that by using a terminal amino hyperbranched polyamide composite porogen when synthesizing polystyrene microspheres, more adsorption sites and diffusion channels are provided for the heat-stable salt ions, which greatly increases the contact area between the purification resin and the heat-stable salt, thereby significantly improving the removal rate of the heat-stable salt.
[0101] By adding methyl methacrylate or ethyl methacrylate during the synthesis of polystyrene microspheres, the polymer main chain structure of the polystyrene microspheres is optimized. According to the principle of like dissolves like, the affinity between the polymer with polar ester groups and the heat-stable salt is enhanced, thereby improving the resin's ability to adsorb and remove the heat-stable salt.
[0102] In the subsequent preparation process of step 3, plasma treatment and immersion in silane coupling agent solution are used to graft molecular chains containing functional groups such as siloxy groups on the resin surface. The siloxy groups can form chemical bonds or complexes with certain ions in the heat-stable salt to enhance the adsorption of the heat-stable salt. In addition, the grafted silane coupling agent molecular chains can change the hydrophilicity and hydrophobicity of the resin surface, making it more conducive to interacting with the heat-stable salt ions, thereby improving the removal efficiency of the heat-stable salt.
[0103] It can be seen from Examples 1 to 3 that by optimizing the distribution ratio of each component and the reaction conditions, the removal rate of the heat-stable salt in the amine solution is kept within a good range.
[0104] As can be seen from Examples 3 to 8, by introducing ion imprinted polymer A and ion imprinted polymer B, the adsorption function and active sites of the purification resin are enriched, and they cooperate with the resin matrix to form a more powerful adsorption system. This system can not only specifically remove sulfate and carbonate heat-stable salts, but also produce a certain adsorption effect on other heat-stable salt ions, thereby improving the overall removal ability of the resin for different types of heat-stable salt ions, and thus improving the removal rate of the total amount of heat-stable salts in the amine solution.
[0105] It can be seen from Examples 8 to 11 that by adding modified chitosan in the middle stage of the synthesis of polystyrene microspheres, the modified chitosan and polystyrene microspheres can be fully combined to form a dispersed system with a special microstructure, which increases the specific surface area and provides more adsorption sites for heat-stable salt ions, thereby enhancing the adsorption effect of heat-stable salts.
[0106] During the synthesis of polystyrene microspheres, the addition of triallyl isocyanurate can significantly improve the mechanical strength and hardness of the polystyrene microspheres. Through the observation of the ion exchange column during the experiment, under the same operating conditions, the column filled with purification resin prepared by adding triallyl isocyanurate did not show obvious resin breakage or deformation during long-term operation, making it less likely to be damaged or deformed in subsequent applications, allowing it to maintain good morphology and performance under different environmental conditions, thereby improving the subsequent purification resin adsorption stability and adsorption efficiency.
[0107] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A process for preparing an amine liquid purification resin for a carbon capture system, characterized in that: The steps include: S1: Styrene, divinylbenzene, acrylate, initiator, porogen, dispersant and water are mixed evenly, heated to 65-100°C, polymerized for 4-8 hours, cooled, solid-liquid separated, porogen extracted, washed and dried to obtain polystyrene microspheres; S2: uniformly mix polystyrene microspheres, chloromethyl methyl ether, Lewis acid catalyst and solvent, heat to 30-50°C, react for 6-8h, cool, separate solid from liquid, wash and dry to obtain chloromethylated polystyrene microspheres; S3: uniformly mix chloromethylated polystyrene microspheres, triethylenetetramine, tetrabutylammonium bromide, antioxidant and ethanol, heat to 80-100°C, react for 10-20 hours, cool, separate solid from liquid, wash, dry, and after plasma treatment, immerse in a silane coupling agent solution with a pH of 8-10 for 2-4 hours, separate solid from liquid, wash, and dry to obtain a purification resin; The mass ratio of styrene, divinylbenzene, acrylate and porogen is 1:(0.1-0.3):(0.1-0.15):(1-1.5); the porogen includes hyperbranched polyamide and dodecane.
2. The process for preparing the amine liquid purification resin for carbon capture system according to claim 1, characterized in that: The mass ratio of the polystyrene microspheres, chloromethyl methyl ether and Lewis acid catalyst is 1:(2-4):(0.1-0.2).
3. The process for preparing the amine liquid purification resin for carbon capture system according to claim 2, characterized in that: The mass ratio of the chloromethylated polystyrene microspheres to triethylenetetramine and tetrabutylammonium bromide is 1:(1-3):(0.008-0.02).
4. The process for preparing the amine liquid purification resin for carbon capture system according to claim 1, characterized in that: The mass ratio of the hyperbranched polyamide to dodecane is (1-3):(1-2).
5. The process for preparing the amine liquid purification resin for carbon capture system according to claim 3, characterized in that: In step S3, when adding triethylenetetramine, the step of adding triethylamine is also included, and the amount of triethylamine used is 10% to 30% of the mass of triethylenetetramine.
6. The process for preparing the amine liquid purification resin for carbon capture system according to claim 1, characterized in that: The silane coupling agent solution comprises 3-aminopropyltriethoxysilane, ethanol and water. The mass fraction of the silane coupling agent solution is 4% to 6%, and the mass fraction of the ethanol is 20% to 40%.
7. The process for preparing the amine liquid purification resin for carbon capture system according to claim 1, characterized in that: In step S1, when adding styrene, the step of adding ion-imprinted polymer A is also included. The preparation method of the ion-imprinted polymer A comprises the following steps: after uniformly mixing sodium sulfate, methacrylic acid and acetonitrile aqueous solution, adding ethylene glycol dimethacrylate and azobisisobutyronitrile in an inert atmosphere and uniformly mixing, heating to 60-80° C., reacting for 12-24 hours, cooling, solid-liquid separation, washing, crushing, acid eluting, washing, and drying to obtain the ion-imprinted polymer A; The molar ratio of sodium sulfate to methacrylic acid is 1:(1.5-2.5); the molar ratio of ethylene glycol dimethacrylate to methacrylic acid is (3-5):1; and the amount of the ion-imprinted polymer A is 10%-20% of the mass of styrene.
8. The process for preparing the amine liquid purification resin for carbon capture system according to claim 1, characterized in that: In step S1, when adding styrene, the step of adding ion-imprinted polymer B is also included; The preparation method of the ion-imprinted polymer B comprises the following steps: after sodium carbonate, acrylic acid and water are uniformly mixed, pentaerythritol tetraacrylate and an oxidation-reduction initiator are added and mixed uniformly under an inert atmosphere, the temperature is raised to 60-80° C., reacted for 6-8 hours, cooled, solid-liquid separation, washing, crushing, acid elution, washing, and drying to obtain the ion-imprinted polymer B; The molar ratio of sodium carbonate to acrylic acid is 1:(2-3); the molar ratio of pentaerythritol tetraacrylate to acrylic acid is (1-2):1; and the amount of the ion-imprinted polymer B is 5%-10% of the mass of styrene.
9. The process for preparing the amine liquid purification resin for carbon capture system according to claim 1, characterized in that: In step S1, after the polymerization reaction starts, a step of adding modified chitosan is also included. The preparation method of the modified chitosan includes the following steps: Under an inert atmosphere, chitosan is dissolved in a dilute acetic acid solution, cooled to 0-5°C, acetic anhydride is added, reacted for 4-6 hours, neutralized, solid-liquid separated, washed, dried, added to N,N-dimethylformamide, and then pyridine and trimethylsilyl chloride are added and mixed evenly, reacted at 20-30°C for 2-4 hours, solid-liquid separated, washed, and dried to obtain modified chitosan; The mass ratio of chitosan, acetic anhydride, pyridine and trimethylchlorosilane is 10: (1.5-2.5): (0.75-1): (0.9-1.2); the amount of modified chitosan is 4%-8% of the mass of styrene.
10. The process for preparing the amine liquid purification resin for carbon capture system according to claim 1, characterized in that: In step S1, when adding divinylbenzene, the step of adding triallyl isocyanurate is also included, and the amount of triallyl isocyanurate is 3% to 6% of the mass of styrene.
Citation Information
Patent Citations
Preparation method of ion exchange resin for removing thermostable salt in alcohol amine solution
CN104725541A
Reactive microsphere
JP1996133990A